2008
DOI: 10.1111/j.1479-828x.2008.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative frozen section in the diagnosis of ovarian tumors

Abstract: Frozen section appears to be an accurate technique for the histopathological diagnosis of ovarian tumours. Some limitations were observed among borderline and mucinous tumours. This emphasises the great value of frozen section in the diagnosis of ovarian tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…The pathologist of other sections may not be familiar with diagnostic clues and FS may become difficult. In spite of these disadvantages overall diagnostic accuracy of FS was reported to be reliable in large series ranging from 84.25% to 97.1%, which was 96.5% in our study (1,(3)(4)(5)(6)(7). We think that attendance of the gynecopathologist to gross examination is a very important factor to increase the diagnostic accuracy of FS.…”
Section: Discussionmentioning
confidence: 74%
“…The pathologist of other sections may not be familiar with diagnostic clues and FS may become difficult. In spite of these disadvantages overall diagnostic accuracy of FS was reported to be reliable in large series ranging from 84.25% to 97.1%, which was 96.5% in our study (1,(3)(4)(5)(6)(7). We think that attendance of the gynecopathologist to gross examination is a very important factor to increase the diagnostic accuracy of FS.…”
Section: Discussionmentioning
confidence: 74%
“…According to considerable amounts of evidence, the sensitivity and specificity of frozen section examination can be as high as 92.8%-100% and 81%-98% for benign ovarian tumors and 87%-100% and 99%-100% for malignant ovarian tumors, respectively. However, the sensitivity and specificity for borderline ovarian tumors can be as low as 33.3%-78.3% and 92%-97%, respectively (14,15). Unfortunately, the diagnostic accuracy based on frozen section examination for ovarian leiomyomas remains unknown due to the rarity of these tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have suggested that under diagnosis was due to sampling errors and they advised using greater number of frozen sections to minimize the under diagnosis of tumors, recommending one section per 10cms of mass. some recent studies have indicated that after sampling errors, the absence of an expert pathologist is responsible for the misdiagnosis of tumors [19,20,21] . In addition pathologists should be informed about tumor status, peritoneal implants and the contra lateral ovary.…”
Section: Discussionmentioning
confidence: 99%